2015
DOI: 10.3109/09513590.2014.1000850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of assisted reproductive technology and of women’s quality of life on depressive symptoms in the early postpartum period: a prospective case-control study

Abstract: This study explored the influence of both assisted reproductive technology (ART) and reduced quality of life (QoL) during pregnancy on postpartum blues (PPB). Sixty-three sub-fertile patients who conceived through ART and 72 women who naturally conceived were enrolled in this prospective study. At 22nd and 32nd gestational weeks, women completed the Edinburgh Postnatal Depression Scale (EPDS) and the Short-Form 36 (SF-36), to investigate depressive symptoms and QoL, respectively; EPDS was again used at 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…Successful conceiving usually needs three or more cycles of assisted reproductive technology. Women experience greater physical and mental stress, as well as higher cost during these processes pregnancy planning period (Dornelles, Maccallum, Lopes, Piccinini, & Passos, ), let alone the high miscarriage risk in the first trimester of pregnancy (Monti et al, ). Our study showed that life events during pregnancy were risk factors for antenatal depression, which is in line with the result of previous study (Meijer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful conceiving usually needs three or more cycles of assisted reproductive technology. Women experience greater physical and mental stress, as well as higher cost during these processes pregnancy planning period (Dornelles, Maccallum, Lopes, Piccinini, & Passos, ), let alone the high miscarriage risk in the first trimester of pregnancy (Monti et al, ). Our study showed that life events during pregnancy were risk factors for antenatal depression, which is in line with the result of previous study (Meijer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by the fact that the participants were assigned to three groups based on their mode of conception, but the details of the infertility treatments, such as the cause of infertility and the number of ART cycles, were not considered. 11 In addition, an exclusion criterion of this study was the presence of any mental disorder during pregnancy. It did not include mothers with the presence of any mental disorder during pregnancy; therefore, women with perinatal depression following ART might not have been included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A population‐based sample of women in the USA who had conceived following any infertility treatment also had no increased risk of post‐partum depressive symptoms . In contrast, an Italian study found that the number of ART cycles, but not the number of conventional infertility treatments, was a factor that predicted the post‐partum psychological state …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other potential relevant risk factors include sociodemographic factors (abuse, stable relationship, financial difficulties etc. ), obstetric complications and the use of reproductive therapies [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%